2011
DOI: 10.1007/978-3-642-23774-4_48
|View full text |Cite
|
Sign up to set email alerts
|

The Perception of Sound and Its Influence in the Classroom

Abstract: Abstract. In this paper we describe a game to assess if the quantitative and graphical perception of sound by students can influence how they behave in the classroom. The game captures sound and shows the sound wave or the frequency spectrum, integrated with an animated character, to students in real time. The quieter the students are the higher the score. A survey was conducted to teachers from an elementary and secondary school to determine if they considered that noise, caused by the students, was a problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…A video projector, connected to the computer where the game is running, shows the animated character to all students. The classes where the game was tested became quieter [12].…”
Section: Results To Datementioning
confidence: 99%
See 1 more Smart Citation
“…A video projector, connected to the computer where the game is running, shows the animated character to all students. The classes where the game was tested became quieter [12].…”
Section: Results To Datementioning
confidence: 99%
“…All the mentioned games comply with our research objective of merging the real world with games, in a way that is easy for the player, and making use of functionality already available in devices such as computers, portable computers and mobile phones. The Castle of Count Pat only needs a low end computer, a microphone and a video projector to show the output of the game to students [12]. The Imaginary Friend resorts to a mobile phone, to an electrodermal activity sensor and to a pico projector.…”
Section: Results To Datementioning
confidence: 99%
“…Van Tonder [60] concluded that most teachers were able to keep classroom noise to a minimum with the help of SoundEarII. Similarly, [13], [61], [75] were able to reduce the average level of noise when the used the visual feedback system.…”
Section: A Theoretical Frameworkmentioning
confidence: 93%
“…Bridging the research on ambient displays to provide feedback and noise within classrooms, Reis and Correia [62] created a serious game to raise awareness on a specific topic, and introduced characters presented on ambient displays that changed their appearance depending on the level of noise. The reported results suggest that the noise means measured by the microphone in 4 groups decreased 39%, 26%, 21%, and 5% respectively as a result of the intervention.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation